Tuning the Electronic and Transport Properties of Three Configurations of Penta-Graphene Nanoribbons - Balvasi, M.; Avazpour, A.; Jalilian, J.; Bidsardare, M.Z. (Acta Physica Polonica A, 2023)
We investigated the effects of the strain, edges, and width of penta-graphene nanoribbons on their electronic structure and transport properties using tight-binding approximation. We considered three different geometries of penta-graphene nanoribbons. In the first case, both the upper and lower edges have a zigzag shape. In the second case, the upper edge has a zigzag pattern, and the lower edge has a beard shape. In the third case, both the upper and lower edges are considered to be beard-shaped. The hopping parameters were evaluated based on Slater–Koster integrals. The Slater–Koster coefficients were evaluated using the TBStudio software package. In our model, we do not apply arbitrary amounts of strain to the structure. For the stability of the structure, we chose the allowable amounts of strain by using the calculated strain–stress curve. Based on the tight-binding approximation, the magnitude of the bandgap in each type of penta-graphene nanoribbon is reduced as the applied strain increases. In addition, the band structures of the three geometries changed, and the bandgap decreased with an increase in width. Hence, such configurations of penta-graphene nanoribbons are expected to be widely used in nano-electronic devices. Finally, we investigated transport properties using a tight-binding model and a generalized Green's function method in the Landauer–Buttiker formalism. By tuning the width of the penta-graphene nanoribbons and applying strain, the maximum current and a lower threshold voltage are achieved. With an increase in the width of the nanoribbon, the intensity of the current and the available energy levels have increased. Our calculated results may suggest potential applications of penta-graphene nanoribbons in spin electronics, nano-electronic devices, and solar cells. In addition, we provide theoretical guidance for regulating the properties of penta-graphene nanoribbons by applying strain, edge modifications, and different widths.